The challenges of the pastoral vocation in the light of historical and social changes a historical overview of unitarian ministerial duties - Bálint Róbert Zoltán (Belvedere Meridionale, 2025)
This paper examines the evolution of Unitarian ministerial roles in the context of historical and social changes. The research employs sociological and historical methods to analyze the regulatory framework governing ministerial work, theological education, and the competencies required for fulfilling ministerial duties. Based on Blizzard’s model, the ministerial role comprises three interconnected levels: traditional roles (preacher, teacher, liturgist), neo-traditional roles (pastoral care), and contemporary roles (community organizer, administrator). Findings indicate that while traditional roles remain strictly regulated, neo-traditional and contemporary roles allow for greater flexibility, enabling ministers to engage in a broader range of activities, including social services, cultural initiatives, and economic development. The study also highlights a shift in emphasis within ministerial roles, with increasing attention given to community-building, social work, and public engagement.